1991
DOI: 10.1530/jrf.0.0930491
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro penetration of pig oocytes matured in culture by frozen-thawed ejaculated spermatozoa

Abstract: Summary. Pig oocytes matured in culture were inseminated with frozen\p=n-\thawed ejaculated spermatozoa without preincubation in modified tissue culture medium (TCM) 199. High penetration rates (85\p=n-\89%) and increased incidence of polyspermy were obtained at 25\p=n-\100\m=x\106 spermatozoa/ml. Wide variation in penetration rates (16\p=n-\89%) was observed in oocytes inseminated in medium containing 5mm caffeine and at 25\p=n-\50\m=x\106 spermatozoa/ml obtained from 6 boars, regardless of sperm motility. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 16 publications
4
81
1
2
Order By: Relevance
“…In the pig, polyspermy is dependent on different boars (Sirard et al, 1993;Wang et al, 1991) and on the presence of a high concentration of capacitated spermatozoa during fertilization (Hunter, 1991;Kim et al, 1997a). Xu et al (1996) reported, based on fresh semen from 3 boars of different breeds, that boars and sperm concentration affect the rates of penetration, polyspermy, and male PN formation.…”
Section: Discussionmentioning
confidence: 99%
“…In the pig, polyspermy is dependent on different boars (Sirard et al, 1993;Wang et al, 1991) and on the presence of a high concentration of capacitated spermatozoa during fertilization (Hunter, 1991;Kim et al, 1997a). Xu et al (1996) reported, based on fresh semen from 3 boars of different breeds, that boars and sperm concentration affect the rates of penetration, polyspermy, and male PN formation.…”
Section: Discussionmentioning
confidence: 99%
“…The basic medium used for maturation and fertilization of oocytes in vitro was tissue culture medium 199 (with Earle's salts; Gibco, Grand Island, NY, USA) supplemented with 3.05 mM Dglucose, 2.92 mM hemicalcium lactate, 0.91 mM sodium pyruvate, 75 µg/ml potassium penicillin G, 50 µg/ml streptomycin sulfate and 10% (v:v) fetal calf serum (Gibco). This medium was essentially the same as TCM-199B used by Wang et al [24].…”
Section: Mediummentioning
confidence: 99%
“…Although most previously published pig IVF protocols included a sperm preincubation stage [1][2][3][4]10], successful fertilization without preincubation was reported when using fresh epididymal [4], freshly ejaculated [7], liquid-preserved ejaculated [9] and cryo-preserved ejaculated [13] spermatozoa. However, in all these latter cases, oocytes were only examined for signs of fertilization after more than 12 h of culture.…”
Section: Discussionmentioning
confidence: 99%